Investigating Errors in Sentence Structure and Punctuation in Non-English Department Students’ Writing: Cause and Remedies - Nugraha, Dimas; Fiftinova, Fiftinova (Universitas Pahlawan Tuanku Tambusai, 2026)
Writing accuracy is a vital component of academic communication, especially for students in non-English departments who are required to produce written texts in English despite limited linguistic training. This study investigates sentence structure and punctuation errors in the writing of non-English Department students at Sriwijaya University, identifies the causes of these errors, and suggests possible remedies to improve students’ writing competence. Using a qualitative descriptive research design, the study analyzed narrative and descriptive essays written by 20 undergraduate students from four non-English study programs in the Faculty of Teacher Training and Education. The analysis was conducted using Corder’s (1974) Error Analysis framework, which classifies errors into omission, misformation, misordering, and addition. To enrich the findings, semi-structured interviews were also carried out with selected students to explore their writing experiences, perceived difficulties, and strategies for dealing with writing problems. The findings show that sentence structure errors occurred more frequently than punctuation errors. Misformation errors were the most dominant type of sentence structure errors, particularly involving incorrect verb forms, tense misuse, and subject–verb disagreement, followed by omission errors such as missing subjects or auxiliary verbs. Punctuation errors mainly included the omission of periods at the end of sentences, misuse of commas, capitalization errors, and incorrect use of apostrophes. Interview data revealed that limited grammar mastery, first language interference, insufficient writing practice and feedback, and psychological factors such as low confidence and time pressure were the main causes of these errors. Overall, the study concludes that sentence structure and punctuation errors among non-English Department students are influenced by a combination of linguistic, instructional, and psychological factors, highlighting the need for grammar-integrated writing instruction, focused feedback, and continuous writing support to enhance students’ academic writing accuracy and clarity.